Potential of Islamic microfinance: issues, challenges and way forward - Redzuan, Nur Harena; Kassim, Salina; Rosman, Romzie; Muhammad Zuki, Mohd Faizuddin; Shaharuddin, Siti Saffa (2022)
Microfinance is an important tool in promoting financial inclusion, which has attracted global attention. More countries are offering microfinance with the support of the government, specialized organizations, and financial institutions. Microfinance is regarded as a means to promote inclusive growth. Therefore, this study analyzes the issues, challenges, and way forward of Islamic microfinance. The study employs a qualitative research method by reviewing the selected literature using content analysis. Islamic microfinance has proved to be more effective in reducing poverty and improving socio-economic conditions. Although it takes a considerable number of resources and funds and many years to convert and adapt conventional microfinance to Islamic microfinance, it has a significant role to play in a Muslim-majority country to promote growth and prosperity among the poor. The study may significantly contribute toward the sustainable and socially impactful growth of the Islamic micro-finance, especially in achieving the maqasid Shariah and Sustainable Development Goals (SDGs). The originality of this study may contribute to the formation of a new body of knowledge and enrich the literature sources in the field of Islamic microfinance that will benefit both academicians and practitioners.